More Than a Social Justice Project: The Continued Road Towards Truth and Reconciliation - Burm, Sarah (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2016)
This community story describes one committee’s experiences in reconciliation after the planning and hosting of an education conference entitled It Matters to Us: Transforming the Legacy of Residential School at Western University’s Faculty of Education. The objective in hosting this conference was to provide educational opportunities that foster dialogue, reconciliation, and relationship building between Indigenous and non-Indigenous peoples. This conference sought to increase knowledge, enhance self-awareness and strengthen the skills of those who work both directly and indirectly with Indigenous peoples. Outlined throughout the story are both the lessons learned and challenges experienced when a group of individuals from diverse individual, familial, and communal backgrounds come together to engage in a process of reconciliation.